Learning Disability Subtypes in Neurofibromatosis 1 - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
An analysis of neuropsychological data for 72 children, aged 6 to 18 years, with neurofibromatosis 1 (NF-1) and academic deficiencies is reported from the University of Texas MD Anderson Cancer Center, Houston, TX.